Characterization of Risk Factors for Neural Tube Defects: A Case-Control Study in Bogota and Cali, Colombia, 2001-2018. (June 2021) - Salazar-Reviakina, Alexander; Sierra-Bretón, Manuela; Rumbo, Jose; Madariaga, Ithzayana; Tovar, Catherin; Uribe, Mateo; Sequera, Carolina; Rodríguez, Catherin; Holguín, Jorge; Sarmiento, Karen; Hurtado-Villa, Paula; Zarante, Ignacio
Worldwide prevalence of neural tube defects is between 1.2 and 124.1 per 10 000 live births. This study analyzes risk factors linked with neural tube defects. The study focused on the Surveillance and Monitoring Programs of Congenital Anomalies databases in Bogota and Cali. Births were monitored between 2001 and 2018. Liveborn or stillborn with neural tube defects were defined as cases, using a case-control ratio of 1:4. Paternal age, folic acid supplementation, birth weight, urban or rural origin, maternal and paternal studies, and socioeconomic levels were analyzed. Across the 215 730 births monitored, 147 cases with a rate of 6.82/10 000 live births were found (6.79-6.85). In isolated cases, lower birth weight had a P <.01. Paternal age >45 years showed an odds ratio (OR) of 4.24 (1.54-11.65), socioeconomic status 1 and 2, OR of 2.49 (1.63-3.82), maternal primary schooling or lower OR 2.61 (1.28-5.31), and housing in urban areas OR 2.4 (1.4-4.09).